ATP6V0A2‐related cutis laxa in 10 novel patients: Focus on clinical variability and expansion of the phenotype. Issue 10 (20th August 2018) - Beyens, Aude; Moreno‐Artero, Ester; Bodemer, Christine; Cox, Helen; Gezdirici, Alper; Yilmaz Gulec, Elif; Kahloul, Najoua; Khau Van Kien, Philippe; Ogur, Gonul; Harroche, Annie; Vasse, Marc; Salhi, Aïcha; et al.
Abstract: In ATP6V0A2 ‐related cutis laxa, the skin phenotype varies from a wrinkly skin to prominent cutis laxa and typically associates with skeletal and neurological manifestations. The phenotype remains incompletely characterized, especially in adult patients. Glycosylation defects and reduced acidification of secretory vesicles contribute to the pathogenesis, but the consequences at the clinical level remain to be determined. Moreover, the morphology of the elastic fibres has not been studied in ATP6V0A2 ‐related cutis laxa, nor its relation with potential clinical risks. We report on the extreme variability in ATP6V0A2 ‐related cutis laxa in 10 novel patients, expand the phenotype with emphysema and von Willebrand disease and hypothesize on the pathogenesis that might link both with deficiency of glycosylation and with elastic fibre anomalies. Our data will affect clinical management of patients with ATP6V0A2 ‐related cutis laxa.